A survey of infectious diseases and vaccination uptake in long‐term hematopoietic stem cell transplant survivors in Australia. Issue 2 (16th January 2019) - Dyer, Gemma; Gilroy, Nicole; Brice, Lisa; Kabir, Masura; Gottlieb, David; Huang, Gillian; Hogg, Megan; Brown, Louisa; Greenwood, Matt; Larsen, Stephen R.; Moore, John; Hertzberg, Mark; et al.
Abstract: Background: This cross‐sectional survey aimed to establish the prevalence of infectious diseases and vaccination uptake in long‐term allogeneic hematopoietic stem cell transplants (HSCT) survivors in New South Wales, in order to reduce long‐term post‐HSCT morbidity and mortality and enhance long‐term care. Patients and methods: Hematopoietic stem cell transplants survivors aged over 18 years and transplanted between 2000‐2012 in New South Wales (NSW) were eligible to participate. Survivors self‐completed the Sydney Post BMT Study survey, FACT‐BMT (V4), Chronic Graft versus Host Disease (cGVHD) Activity Assessment Self Report, Lee Chronic GvHD Symptom Scale, DASS21, Post Traumatic Growth Inventory, and the Fear of Recurrence Scale. Results: Of the 583 HSCT survivors contacted, 441 (78%) completed the survey. Respondents included 250 (57%) males and median age was 54 years (range 19‐79 years). The median age at the time of transplant was 49 years (Range: 17‐71), the median time since HSCT was 5 years (Range: 1‐14) and 69% had cGVHD. Collectively, 41.7% of survivors reported a vaccine preventable disease (VPD) with the most common being influenza‐like‐illness (38.4%), varicella zoster/shingles (27.9%), pap smear abnormalities (9.8%), pneumococcal disease (5.1%), and varicella zoster (chicken pox) (4.6%). Only 31.8% had received the full post‐HSCT vaccination schedule, and the majority (69.8%) of these had received the vaccines via their General Practitioner. cGVHD was not found to be a significant factor on multivariate analysis for those who were vaccinated. There was a trend toward lower vaccination rates in patients in a lower income strata. Conclusions: Vaccinating post‐HSCT survivors to prevent infections and their consequences have an established role in post‐HSCT care. Improving rates of post‐HSCT vaccination should be a major priority for BMT units.